Dhritarashtra’s embrace: big and small parties in Kerala and Tamil Nadu - K. K. Kailash
Why do we find more parties from Tamil Nadu in the Lok Sabha compared to Kerala and why are there more parties in the legislative assembly in Kerala compared to Tamil Nadu? This incongruence is puzzling since elections to both levels of government, federal and state, are based on the single-member simple plurality electoral system and the territorial boundaries of the state, and therefore the societal environment remains constant. This article argues that this incongruence is not merely the product of the federal parliamentary structure of the polity, electoral rules, and socio-economic factors but because of what parties do. This article gives agency to parties and brings party strategy to the centre of the analysis.